Outfoxed - McMullen-Ciotti, Elise (Wish (Scholastic Inc.), 2025)
"Twelve-year-old Skye has just rescued a baby fox she's named Kitkat, with the help of her Park Ranger cousin Braeden. Skye would usually release the fox back into the wild as soon as it's healed, but this baby fox was injured by a trap. No one hurts a baby animal and gets away with it as long as Skye's around, and now she's on a mission to find the poacher! When Skye takes Kitkat to the vet, she meets a quiet girl named Ivy. To Skye's surprise, Ivy decides to join in on the investigation and a friendship starts to form between the girls. But will these new friends uncover the true identity of the poacher and safely release Kitkat back into the wild?"--Provided by publisher.